Peranan Teknologi dalam Optimalisi Pengelolaan Container Yard (CY) pada PT. Masaji Kargosentra Tama Belawan - Dea Sabrina; Syarifur Ridho; Fahmi Rinaldi; Fadiyah Hani Sabila (Jurnal Transformasi Bisnis Digital, 2024)
This paper explains the role of technology in optimizing container yard (CY) management at PT. Masaji Kargosentra Tama Belawan. PT. Masaji Kargosentra Tama Belawan is a shipping company that is a multimodal transport business entity, this company operates in the field of domestic warehousing services and import and export container Freight Station (CFS), with warehouse supply and distribution services. The container yard is one of PT's main facilities. Masaji Kargosentra Tama Belawan is used to form containers to minimize the risk of ship delays resulting in decreased loading and unloading production. In managing container yards, there are obstacles, including incompetent human resources and high implementation costs. For this reason, the purpose of writing this paper is to determine the role of technology in optimizing container yard (CY) management. The method used in this writing is field research (field research) where the author makes direct observations at the company and library research (library research) where the author obtains paper material from books in the library or other reading sources related to the main points. taken is the Role of Technology in Optimizing Container Yard (CY) Management at PT. Masaji Kargosentra Tama Belawan.